2018
DOI: 10.5539/ijb.v10n4p23
|View full text |Cite
|
Sign up to set email alerts
|

The Histological Effect of Aqueous Ginger Extract on Kidneys and Lungs of Diabetic Rats

Abstract: Diabetes is a disorder affecting various-aged humans and which can with time cause serious problems for the patient. Medicinal plants are known for their hypoglycemic effects; and among which is ginger (Zingiber officinale) known also for its culinary uses. This study, therefore, was undertaken to evaluate the histological effect of 21-day treatment of aqueous ginger extract used at 500 mg / kg BW on female diabetic rats. Fifteen female albino rats were divided into three groups; Group I: control, Group II: no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The present study showed that ginger results in partial improvement of diabetic changes in the lung causing decreased the thickening of the interalveolar septa, widening of the alveolar lumen and decreased inflammatory cell infiltration and thickness of blood vessels wall. These findings are in agreement with other study [26] . They found that ginger improved changes in lung caused by diabetes such as inflammatory cell infiltration and degeneration of bronchiolar epithelium.…”
Section: Discussionsupporting
confidence: 94%
“…The present study showed that ginger results in partial improvement of diabetic changes in the lung causing decreased the thickening of the interalveolar septa, widening of the alveolar lumen and decreased inflammatory cell infiltration and thickness of blood vessels wall. These findings are in agreement with other study [26] . They found that ginger improved changes in lung caused by diabetes such as inflammatory cell infiltration and degeneration of bronchiolar epithelium.…”
Section: Discussionsupporting
confidence: 94%
“…Intervention durations ranged from 2 to 16 weeks. Location of studies performed as follows: 9 in Egypt [15][16][17][18][19][20][21][22][23], 8 in India [24][25][26][27][28][29][30][31], 6 in Saudi Arabia [32][33][34][35][36][37], 4 in Iran [38][39][40][41], 3 in Kuwait [42][43][44], 3 in Pakistan [45,46], 2 in Nigeria [47,48], 2 in China [49,50], 1 in South Korea [51], Jordan [52], Iraq [53] and Malaysia [54]. Studies were done from 2006 to2021.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Intervention duration ranged from 2 to 16 weeks. Location of studies performed as follows: 9 in Egypt [29,30,35,37,38,47,48,54,59], 8 in India [26,36,39,41,42,49,51,56], 6 in Saudi Arabia [22,23,44,45,52,61], 4 in Iran [31][32][33]53], 3 in Kuwait [34,57,58], 3 in Pakistan [28,46,55], 2 in Nigeria [24,43], 2 in China [21,27], 1 in South Korea [25], Jordan [50], Iraq [60] and Malaysia [40]. Studies were done from 2006 to 2021.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%